2014
DOI: 10.1007/s00267-014-0407-7
|View full text |Cite
|
Sign up to set email alerts
|

Valuing the Recreational Benefits of Wetland Adaptation to Climate Change: A Trade-off Between Species’ Abundance and Diversity

Abstract: Climate change will further exacerbate wetland deterioration, especially in the Mediterranean region. On the one side, it will accelerate the decline in the populations and species of plants and animals, this resulting in an impoverishment of biological abundance. On the other one, it will also promote biotic homogenization, resulting in a loss of species' diversity. In this context, different climate change adaptation policies can be designed: those oriented to recovering species' abundance and those aimed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…Studies by Qiu et al [13] and Dallimer et al [16] showed that people's recreational preferences are not related to biodiversity, but some studies have found that people preferred an environment with rich and diverse plants [15,31,32]. This study found that people's preferences have a positive correlation with species richness, and the degree of preference significantly differed in the different habitats.…”
Section: Perception and Preference Of Biodiversity In The Different Hmentioning
confidence: 60%
“…Studies by Qiu et al [13] and Dallimer et al [16] showed that people's recreational preferences are not related to biodiversity, but some studies have found that people preferred an environment with rich and diverse plants [15,31,32]. This study found that people's preferences have a positive correlation with species richness, and the degree of preference significantly differed in the different habitats.…”
Section: Perception and Preference Of Biodiversity In The Different Hmentioning
confidence: 60%
“…Two DCEs were designed to capture the effect of uncertainty on individuals' preferences for conservation policies. One DCE, used here as a control treatment and presented in Faccioli et al (2015), illustrated a context in which CC impacts and the results of policies in S'Albufera were displayed as certain to respondents (certain treatment). In the second DCE, both CC impacts and, consequently, the results of policies appeared as uncertain (uncertain treatment).…”
Section: Choice Experiments Designmentioning
confidence: 99%
“…Studies around wetlands [88,89], coastal waters [49,86] and MPAs [6,90] also point to the importance of cooperating with natural scientists to obtain information about environmental uncertainties and potential irreversibilities. As the way people process and interpret uncertainty and irreversibility risk can affect ecosystem values, such information is crucial to avoid biased estimates.…”
Section: C) Need For Inter-disciplinary Cooperation With Natural Sciementioning
confidence: 99%